PENGEMBANGAN MEDIA PUZZLE GAMBAR SERI UNTUK KETERAMPILAN MENULIS KARANGAN SEDERHANA BAHASA JERMAN SISWA KELAS XII SMA - ROSATI, MUFIKA (LATERNE, 2016)
In German classes, students need a learning medium, especially in writing. Puzzle picture story is a medium thatcan be used in German learning. Based on NEEDS questionnaire, which were provided in the XII SMAN 13 Surabaya class, there are 55.17% students who have difficulty in writing. And there are 62.07% of students who are interested in learning media. Also a learning medium is needed. The media can help the students to help the writting skills. This study has the formulation of the problem: "What is the development process of the puzzle picture story for the skill of writing simple essay the student class XII SMA ?. The aim of this study is describing the development process of learning medium "Puzzle Picture Story" for the skill of writing simple essay in German classes Class XII SMA. This study have 6 steps, based on the theories of Sadiman Arif. The steps are (1) identifying the needs of students; (2) Formulation of targets; (3) formulation of the material; (4) formulation of success measurement tools; (5) the formulation of media texts; (6) validation. The results of this study are: (1) Validate media experts assessed to 90.63% with the evaluation criteria "very strong". (2) and the validation from the materien expert shows that 88.63% of the evaluation criteria "very strong". In concluded, it can be written that the media puzzle developed picture story feasible for simple essay writing German university class to use XII. Keywords : media, puzzle picture story, writing skills.